RANCANG BANGUN PORTABLE MATERNAL ELECTROCARDIOGRAM BERBASIS BLIND SOURCE SEPARATION UNTUK MONITORING AKTIVITAS JANTUNG IBU HAMIL - Asrori, Ahmad; Wafi, Mohammad Kamalul; Pambudi, Ikrarda Tegar; Hasan, Ola Dwi Sandra (Program Kreativitas Mahasiswa - Karsa Cipta, 2013)
Design and implementation of Portable Maternal Electrocardiogram using Blind Source Separation algorithm done to make a portable instrument and capable of separating signals electrocardiogram mother with fetus without removing some of its parts. From the experiment, at the midwife practising house, the instrument has successfully separate signal maternal and fetal electrocardiogram. Data retrieval is performed on a 38 years old pregnant woman with gestational age 24 weeks. As a result, mother has a frequency signals electrocardiogram smaller than a fetus. This is in accordance with the theory that the mothers pulse rate ranging between 90-120 times per minute while the fetus ranges between 120-140 times per minute.